INFLUENCE OF VARIOUS FEED ADDITIVES ON THE ACTIVITY OF CHYME AND BLOOD PLASMA ENZYMES OF YOUNG MEAT CHICKEN OF ORIGINAL LINE - A. Grozina (Scientific Journal of Pedagogy and Economics, 2021)
The research aimed to determine the effect of a mixture of low molecular weight organic acids and complex phytobiotics when replacing a feed antibiotic with them on the activity of digestive enzymes in the duodenal chyme and the activity of pancreatic enzymes in the blood plasma of young stock B5 and B9 meat chicken lines. The experiments were carried out on the original lines of meat poultry lines B5 (Cornish) and B9 (Plymouth rock). There was an operation to insert a cannula into the duodenum at the age of 6 weeks. The enzymatic activity of the duodenum chyme and the content of pancreatic enzymes in the blood plasma in the groups of chickens receiving antibiotics, low molecular weight organic acids, and phytobiotics with the diet. The data showed that the influence of feed additives on the physiological status of poultry was different. The use of low molecular weight organic acids of the B5 and B9 chicken lines had a significant effect on the production of digestive enzymes due to an increase in the activity of chyme lipase (by 98.3%) and blood plasma lipase (by 26.6%) in B9 chickens and an increase in chyme proteases (by 30.9%) in B5 chickens compared with the control group, where the antibiotic was used. The introduction of complex phytobiotics into the diet had a negative effect on chickens of the B5 line (Cornish), reducing the activity of amylase and lipase of the duodenal chyme (by 29.2 and 26.9%) compared with the control group. In B9 (Plymouth rock) chickens, only the chyme amylase activity increased by 30.8% that indicates an improvement in the availability of feed carbohydrates. These data confirm the need to take into account the different effects of feed additives on the digestion processes in different poultry crosses.